ASSOCIATION BETWEEN THYROID HORMONES WITHIN NORMAL TO SUBCLINICAL DYSFUNCTION AND LEFT VENTRICULAR DIASTOLIC DYSFUNCTION - Jun, Ji Eun; Lee, Seung Eun; Kim, Tae Hyuk (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Thyroid hormones play critical roles in modulating the cardiovascular system. However, the effects of subclinical thyroid dysfunction and euthyroidism on cardiac function remain unclear. We investigated the association between left ventricular (LV) diastolic dysfunction and subclinical thyroid dysfunction or thyroid hormone levels within the reference range and LV diastolic dysfunction in a large cohort. METHODOLOGY This cross-sectional study included 26,289 participants (22,197 euthyroid, 3,671 with subclinical hypothyroidism, and 421 with subclinical thyrotoxicosis) who underwent regular health checkups. The cardiac structure and function were evaluated using echocardiography. LV diastolic dysfunction with normal ejection fraction (EF) was defined as follows: EF of >50% and (a) E/e’ ratio >15, or (b) E/e’ ratio of 8–15 and left atrial volume index ≥34 mL/m2. RESULTS Subclinical hypothyroidism was significantly associated with cardiac indices regarding LV diastolic dysfunction, and the risk of having LV diastolic dysfunction was also increased in participants with subclinical hypothyroidism (adjusted odds ratio [AOR] 1.36, 95% confidence interval [CI], 1.01–1.89) compared to euthyroid participants. The risk of having diastolic dysfunction was even greater in participants who had relatively severe hypothyroidism (thyroid stimulating hormone [TSH] ≥10.0 uIU/mL (AOR, 1.99; 95% CI: 1.07–5.00). Subclinical thyrotoxicosis was not associated with diastolic dysfunction. Among the thyroid hormones, only serum triiodothyronine (T3) was significantly and inversely associated with LV diastolic dysfunction even within the normal range. CONCLUSION Subclinical hypothyroidism is significantly associated with LV diastolic dysfunction. Subclinical thyrotoxicosis is, in part, associated with changes in the indices of LV structure or function, but its association with the presence of diastolic dysfunction was not significant. Serum T3 is a relatively important contributor to LV diastolic dysfunction compared to TSH or free thyroxine.